2014
DOI: 10.1016/j.jacc.2013.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Endovascular Catheter Core Cooling Combined With Cold Saline as an Adjunct to Percutaneous Coronary Intervention for the Treatment of Acute Myocardial Infarction

Abstract: Hypothermia induced by cold saline and endovascular cooling was feasible and safe, and it rapidly reduced core temperature with minor reperfusion delay. The primary end point of IS/MaR was not significantly reduced. Lower incidence of heart failure and a possible effect in patients with early anterior ST-segment elevation myocardial infarctions need confirmation. (Efficacy of Endovascular Catheter Cooling Combined With Cold Saline for the Treatment of Acute Myocardial Infarction [CHILL-MI]; NCT01379261).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(131 citation statements)
references
References 27 publications
1
129
0
1
Order By: Relevance
“…This favorable experience prompted a multicenter trial of this cooling method in 120 randomized patients. 8 In the hypothermia group, 76% of patients achieved a core temperature <35°C, with door-to-balloon time prolonged by 10 minutes compared with control. There was no significant difference in infarct size normalized to area at risk (median 40.5% with hypothermia versus 46.6% with control, P=0.15).…”
Section: Results From Prior Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…This favorable experience prompted a multicenter trial of this cooling method in 120 randomized patients. 8 In the hypothermia group, 76% of patients achieved a core temperature <35°C, with door-to-balloon time prolonged by 10 minutes compared with control. There was no significant difference in infarct size normalized to area at risk (median 40.5% with hypothermia versus 46.6% with control, P=0.15).…”
Section: Results From Prior Studiesmentioning
confidence: 91%
“…1 Induction of mild hypothermia (<35°C) before reperfusion has been shown to reduce infarct size in animal models of STEMI, 2,3 as well as in small randomized trials and subgroup analyses of larger randomized trials in humans. [4][5][6][7][8][9] As smaller infarct size is strongly correlated with greater ejection fraction and improved survival, systemic hypothermia may have long-term benefits in patients with STEMI. Peritoneal Hypothermia in STEMI ensure adequate cooling before percutaneous coronary intervention (PCI).…”
mentioning
confidence: 99%
“…The clinical evidence for the role of therapeutic hypothermia in limiting infarct size has been more difficult to establish. The clinical hypothermia trials in acute myocardial infarction to date have been limited by small numbers of patients and thereby lacked significant power (22)(23)(24)(25)(26)(27). However, recent pooled or combination analyses of the individual studies have shown consistent clinical benefits of limiting MI size and decreasing the development of heart failure (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the Efficacy of Endovascular Catheter Cooling Combined With Cold Saline for the Treatment of Acute Myocardial Infarction (CHILL-MI) trial randomized 120 patients with STEMI to hypothermia induced by the rapid infusion of 600-2000 ml cold saline and endovascular cooling or standard of care [113]. Hypothermia was initiated before PCI and continued for 1 h after reperfusion.…”
Section: Hypothermiamentioning
confidence: 99%